The Ownership of Enterprise - Hansmann, Henry (Harvard University Press, 2022)
The investor-owned corporation is the conventional form for structuring large-scale enterprise in market economies. But it is not the only one. Even in the United States, noncapitalist firms play a vital role in many sectors. Employee-owned firms have long been prominent in the service professions--law, accounting, investment banking, medicine--and are becoming increasingly important in other industries. The buyout of United Airlines by its employees is the most conspicuous recent instance. Farmer-owned produce cooperatives dominate the market for most basic agricultural commodities. Consumer-owned utilities provide electricity to one out of eight households. Key firms such as MasterCard, Associated Press, and Ace Hardware are service and supply cooperatives owned by local businesses. Occupant-owned condominiums and cooperatives are rapidly displacing investor-owned rental housing.